The New Republic : a Commentary on Book I of More's Utopia Showing Its Relation to Plato's Republic. - Starnes, Colin (Wilfrid Laurier University Press, 2006)
Colin Starnes radical interpretation of the long-recognized affinity of Thomas More's Utopia and Plato's Republic confirms the intrinsic links between the two works. Through commentary on More's own introduction to Book I, the author shows the Republic is everywhere present as the model of the "best commonwealth," which More must first discredit as the root cause of the dreadful evils in the collapsing political situation of sixteenth-century Europe. Starnes demonstrates how More, once having shorn the Republic of what was applicable to a society that had for a thousand years accepted and bee.